Community Answer

Honor CodeSolved 1 Answer

See More Answers for FREE

Enhance your learning with StudyX

Receive support from our dedicated community users and experts

See up to 20 answers per week for free

Experience reliable customer service

Get Started

\begin{array}{l}s(0)=c_{1} \cos 0+c_{2} \sin 0=c_{1}=12 \\s^{\prime}(t)=\frac{-c_{1}}{6} \sin \left(\frac{t}{6}\right)+\frac{c_{2}}{6} \cos \left(\frac{t}{6}\right) \\s^{\prime}(0)=\frac{c_{2}}{6}=0 \Rightarrow c_{2}=0\end{array}Hence, s(t)=12 \cos \left(\frac{t}{6}\right)s(t)=A \cos (\omega t)=12 \cos \left(\frac{t}{6}\right)\Rightarrow Amplitude, A=12, \omega=\frac{1}{6}\begin{array}{l}T=\frac{2 \pi}{w}=\frac{2 \pi}{(1 / 6)}=12 \pi \\V_{\text {max }}=A w=12 \times \frac{1}{6}=2 .\end{array}a) The spring oscillating most quickly (with the shortest perid) is spring no. (ii) with time period \pi / 3=Tb) The spring oscillating with the largest amplitude is spring no. (iv) with amplitude A=12c) The spring oscillating most slowy (with the longest peri(d) is spring no.(iV) with T=12 \pid) The spring oscillating with the largest maximum velocity is sping no. (ii) with v_{\text {max }}=12u200bu200bu200bu200bu200bplease do upvote thankyou!!(i)\begin{array}{c}9 s^{\prime \prime}+s=0, s(0)=6, s^{\prime}(0)=0 \\s^{\prime \prime}=\frac{s}{9}=0 \\\Rightarrow \frac{d^{2} s}{d t^{2}}+\frac{s}{9}=0 \quad \text { where let } \frac{d}{d t}=D \\\Rightarrow\left[D^{2}+\frac{1}{9}\right] s=0 \quad \Rightarrow \quad D^{2}+\frac{1}{9}=0\end{array}So, D= \pm \sqrt{-\frac{1}{9}}= \pm \frac{1}{3} i= \pm \frac{i}{3}D=\frac{ \pm i}{3}=\alpha \pm i \beta \Rightarrow \alpha=0 \text { and } \beta=\frac{1}{3}so, S(t)=\left(c_{1} \cos \beta t+c_{2} \sin \beta t\right) e^{\alpha t}\Rightarrow s(t)=1_{1} \cos \left(\frac{t}{3}\right)+c_{2} \sin \left(\frac{t}{3}\right) \text { where } e^{\circ}=1compare with s(t)=c_{1} cosut +c_{2} sinut\begin{array}{l} \rightarrow \omega=\frac{1}{3} \\S(0)=6 \Rightarrow c_{1} \cos 0+c_{2} \sin 0=6 \\\Rightarrow c_{1}=6\end{array}\begin{aligned}s^{\prime}(t) & =-\frac{c_{1}}{3} \sin \left(\frac{t}{3}\right)+\frac{c_{2}}{3}\left(\frac{t}{3}\right) \\s^{\prime}(0) & =-\frac{c_{1}}{3} \sin (0)+\frac{c_{2}}{3} \cos (0) \\\Rightarrow s^{\prime}(0) & =\frac{c_{2}}{3}=0 \Rightarrow c_{2}=0\end{aligned}Hence, s(t)=6 \cos \left(\frac{t}{3}\right)\Rightarrow s(t)=A \cos (\omega t)=6 \cos \left(\frac{t}{3}\right)So, Amplitude, A=6, \omega=\frac{1}{3} \Rightarrow Time period (t)=\frac{2 \pi}{\omega}\Rightarrow T=\frac{2 \pi}{(1 / 3)}=6 \pi \quad \varepsilon maximum veloity,V_{\max }=A C==6 \times \frac{1}{3}=2(ii)\begin{array}{l}s^{\prime \prime}+36 s=0, s(0)=2 \quad s^{\prime}(0)=0 \\\frac{d^{2} s}{d t^{2}}+36 s=0 \Rightarrow\left(D^{2}+36\right) s=0 \\\text { Henc, } \quad D= \pm \sqrt{-36}= \pm 6 i\end{array}Henc, D= \pm \sqrt{-36}= \pm 6 i\begin{array}{l}s(t)=c_{1} \cos 6 t+c_{2} \sin 6 t \\s(0)=c_{1}=2 \text { and } s^{\prime}(t)=-6 c_{1} \sin 6 t+6 c_{2} \cos 6 t \\s^{\prime}(0)=6 c_{2}=0 \Rightarrow c_{2}=0\end{array}Hence, s(t)=2 \cos 6 t=A \cos (\omega t)\Rightarrow Amplitude, A=2, \omega=6\begin{array}{l}p=\frac{2 \pi}{\omega}=\frac{2 \pi}{6}=\pi / 3 \\V_{\max }=A W=2 \times 6=12\end{array}(iii)\begin{array}{l}s^{\prime \prime}+9 s=0, s(0)=3, \quad s^{\prime}(0)=0 \\\left(D^{2}+9\right) s=0 \Rightarrow \frac{d^{2} s}{d t^{2}}+9 s=0 \\\Rightarrow D^{2}+9=0 \text { which gives } D= \pm \sqrt{-3}= \pm 3 i \\s(t)=c_{1} \cos 3 t+c_{2} \sin 3 t \Rightarrow \quad \text { and } s^{\prime}(t)=-3 c_{1} \sin 3 t+3 c_{2} \cos 3 t \\s(0)=C_{1}=3 \quad s^{\prime}(0)=0 \Rightarrow c_{2}=0\end{array}Henc, s(t)=3 \cos 3 t=A \cos \omega tSo, A=3, w=3, \quad T=\frac{2 \pi}{3}, V_{\max }=3 \times 3=9(iv)\begin{array}{l}36 s^{\prime \prime}+s=0, \quad s(0)=12, \quad s^{\prime}(0)=0 \\s^{\prime \prime}+\frac{s}{36}=\frac{d^{2} s}{d t^{2}}+\frac{s}{36}=0 \\\Rightarrow\left(D^{2}+\frac{1}{36}\right) 5=0 \\s 0, D= \pm \sqrt{-\frac{1}{36}}= \pm \frac{1}{6} i=\alpha \pm i \beta \Rightarrow \alpha=0, \beta=\frac{1}{6} \\s(t)=c_{1} \cos \frac{t}{6}+c_{2} \sin \frac{t}{6}\end{array} ...